Pedagogical grammar as the framework of TEFL research. Part 15. Age and foreign language acquisition: biological, cognitive and affective factors - Chernovaty, L. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2023)
The paper presents a comparative analysis of the three groups of factors (biological (neurological), cognitive and affective), which are believed to be related to the impact of the learnersʼ age on the foreign language acquisition. Having analyzed the available research data concerning the possible role of biological aspects the hypothetic critical age may be based on (laterization, puberty, plasticity of specific brain areas, neuronsʼ maturation time, the thalamus hypothesis), the author formulates the preliminary conclusion about the contradictive data on the issue and the need for further research in the area. The same generally applies to the cognitive and affective aspects of the problem. The age differences in the foreign language learning can only partially be explained by different attitudes to language as an object of acquisition of children and adults considering a wide range of varieties within each of the said groups. The difference in adult and child acquisition strategies can be explained by a number of cognitive factors, such as the strong social attitude to the use of the native and foreign languages, as well as the ability of abstract thinking in adults. The cognitive development can explain why teenagers learn the language better than younger children, but it cannot account for the advantage of teenagers in the field of pronunciation acquisition or the childrenʼs better results in speaking over long periods of time. As far as affective aspects are concerned, many adults have problems in passing through the crucial stage (cultural stress) or they do not pass it through at all. In typical cases of language acquisition, most affective factors in the language environment are unfavorable for adults and favorable or neutral for children, creating unequal learning conditions. At the same time, some adults manage (due to individual and other factors) to approach the affective parameters of the childʼs conditions of acquisition. This may be an explanation for cases of adultsʼ rapid and effective acquisition of the foreign language.